The a to Z of the British and Irish Civil Wars 1637-1660 - Bennett, Martyn (Rowman & Littlefield Publishers, 2010)
During the 17th century, the British Isles were trapped in a 23 year-long state of turmoil through civil war, continued rebellion, and revolutions. King Charles I wanted to instill a new uniform religious policy throughout the British Isles, and this caused a massive uproar over the King's policies toward the diverse people in his empire-the English, Irish, Scottish, and Welsh. No person remained unaffected in the kingdom and eventually King Charles I was executed and the entire system of monarchy tumbled into a short-lived republic. Eventually the monarchy was restored under King Charles II, but the history of the British Isle in the seventeenth century remains forever marked by its tumultuous nature. Through a concise historical chronology and comprehensive overview, users of The A to Z of the British and Irish Civil Wars 1637-1660 will find an insightful explanation of the people, places, and events that indelibly shape the United Kingdom's 17th-century history. The cross-listed dictionary entries offer a complete explanation of each important aspect of the Civil Wars and their effect on the Kingdom. It also includes maps and a bibliography.